Pengaruh Citra Merek Dan Harga Terhadap Kepuasan Pelanggan Pada Toko Budi Market - Zuriani Ritonga; Rizkha Maulana; Karimi Karimi; Sutoyo Sutoyo; Hayanuddin Safri (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of brand image and price on customer satisfaction at the Budi Market Store. The sample used in this research was 100 customers of Toko Budi Market. The method in this research is a quantitative method. The research results show that partially or simultaneously product quality and product variants influence purchasing decisions at the Budi Market Store. Based on the test results, Fcount 84.222 > Ftable 2.70, it can be concluded that the brand image and price variables simultaneously influence customer satisfaction when purchasing products at the Budi Market Bireuen Store.